PENGATURAN RUANG TERBUKA HIJAU DALAM HUKUM TATA RUANG - Adinda, Isep H Insan; Perdana, Angga; Radella Berlian Dewi Kartini; Nabila, Sylvia; Maharani, Adinda Putri; Rosyaputri, Nuradilla Maharani (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2022)
This journal provides an explanation of Green Open Space Regulations, in this lesson the aim is to explain that there are still many cities that do not have proper Green Open Space, therefore in managing Green Open Space a policy management must be implemented to maintain a balance between urban development and environmental preservation along with a perspective from spatial planning law. In the explanation of this journal, there is one example of the implementation of green open space regulation which is still relatively low, namely in the city of Bandung due to an imbalance regarding the human development index which continues to increase. And this journal helps provide in-depth information about the effectiveness of Regional Regulations regarding green open spaces in spatial planning law as well as the impact of green open space development plans on spatial planning in Indonesia. Apart from that, this journal aims to find out about urban areas which are currently a problem that is quite difficult to overcome due to the increasing demand for land. Keywords: law enforcement, green open space, spatial layout